Developing Sustainable Design Strategies for Agritourism Accommodations in Shree Antu, Ilam, Nepal - Pokharel, Pradip (Journal of Engineering Technology and Planning, 2025)
Agritourism is an emerging concept that integrates agriculture with tourism, allowing visitors to engage in farming activities such as planting and harvesting while local producers provide lodging, meals, and guided experiences. Globally, agritourism often emphasizes farming practices, agricultural products, and recreational activities: however, in Nepal, it is distinguished by its focus on local cuisine, handicrafts, and rural hospitality. The research identifies a lack of awareness regarding agritourism, of its hospitality components, and the negative impacts of mass tourism as major challenges in the study area. This paper examines the current state of agritourism in Shree Antu, Ilam, and explores design strategies for sustainable agritourism accommodations. The NOISE framework (Needs, Opportunities, Improvements, Strengths, and Exceptions) is employed to evaluate existing accommodation practices. To better understand visitor perceptions and experiences, Google reviews of local accommodations were analyzed. Drawing on previous research and contextual analysis, the study proposes general architectural planning and design guidelines for agritourism accommodations, including farm stays, cottages, and eco-resorts. The findings emphasize that achieving sustainability requires accommodations to be carefully sited and oriented to capture natural views, constructed with locally sourced materials, and equipped with appropriate thermal insulation across building zones. Ultimately, agritourism accommodations should adhere to sustainable architectural principles while reflecting the local architectural character. The outcome of this research aims to inform architects, property owners, and potential investors, fostering the growth of agritourism and supporting sustainable rural development in Nepal.